Rancang Bangun Aplikasi Augmented Reality sebagai Media Promosi Penjualan Model Kontainer - Adisya Ayustina; Suprianto Suprianto; Hindarto Hindarto (Institut Teknologi Garut, 2023)
In the current technological era, computer technology is increasingly dominating, the role of the computer has now shifted from being used as a calculating machine, now it has penetrated the business world. Many business processes of business owners utilize information technology as an effective and attractive promotional medium. One of them on the CV. PAS TIM is still promoting in general, namely by displaying 2D images using magazines. Therefore the research created a promotional media application program based on augmented reality, where the application functions as a sales promotion media for container models by displaying 3D objects on samples that have been installed with markers, so that with the application of augmented reality technology this makes an attractive promotional media. The methodology used is MDLC (Multimedia Development Life Cycle) which has several stages including concept, design, material collecting, assembly, testing and distribution. Then alpha testing using the Black Box Testing method. From the results of this design, it produces an augmented reality-based sales promotion media application that is interactive, effective and can attract the interest of potential customers.